Active vibration control of a conical shell using piezoelectric ceramics. Issue 4 (December 2017) - Sun, Longfei; Li, Weijia; Wu, Yaozhong; Lan, Qiuhua
Conical shell structures are commonly used in many engineering systems, and vibration suppression is very important to realize the desired function. In this study, piezoelectric ceramics were used as actuators/sensors with a multimodal fuzzy sliding mode controller to suppress vibrations of conical shell structure for the first time. The structure's natural frequencies and mode shapes were obtained through modal analysis using finite element method and verified by modal tests. The agreement between analysis and test results verified the finite element method was appropriate. A multimodal fuzzy sliding mode controller was subsequently designed based on the analysis to provide active vibration control. The resulting controller was tested experimentally for the conical shell structure. The experimental results indicated that the proposed controller can effectively use to suppress vibration for the conical shell structure.